Opportunities and Challenges of Soy Proteins with Different Processing Applications - Zixiao Deng; Sung Woo Kim (MDPI AG, 2024)
Soybean meal (SBM) is a prevailing plant protein supplement in animal diets because of its nutritional value and availability. This review paper explores the significance of SBM and processed soy products, emphasizing their nutritional and bioactive components, such as isoflavones and soyasaponins. These compounds are known for their antioxidant and anti-inflammatory properties and are associated with a reduced prevalence of chronic diseases. However, the presence of antinutritional compounds in SBM presents a significant challenge. The paper evaluates various processing methods, including ethanol/acid wash, enzyme treatment, and fermentation, which are aimed at enhancing the nutritional value of soy products. It highlights the significance to maintain a balance between nutritional enhancement and the preservation of beneficial bioactive compounds, emphasizing the importance of different processing techniques to fully exploit the health benefits of soy-based products. Therefore, this review illuminates the complex balance between nutritional improvement, bioactive compound preservation, and the overall health implications of soy products.